Daily field checking list by Walter Rosene, January 6, 1935 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Bird checklist dated January 6, 1935. This checklist was used by Walter Rosene to record birds sighted around McCaskey pasture and North Bridge with Walter Jr. and Bob Walker between 10:00 and 1:30. Plustek--flatbed